The effect of policy measures, school holidays and travel on the incidence of SARS-CoV-2 infection in children and adults in Estonia from 2021 to 2022 - Hiie Soeorg; Taavi Päll; Aare Abroi; Radko Avi; Olga Sadikova; Mari-Anne Härma; Tuuli Reisberg; Irja Lutsar; Kristi Huik (PLoS ONE, 2025)
Purpose The policy measures implemented during the COVID-19 pandemic, travel and school holidays could have influenced the spread of SARS-CoV-2 infection in children and adults differently. We aimed to determine the effect of policy measures, school holidays and travel on the incidence of SARS-CoV-2 infection in children and adults. Methods The overall SARS-CoV-2 infection incidence between 1 February 2021 and 1 May 2022 was decomposed into the most common lineage-specific incidence per 100,000 by imputing lineage based on the sequencing results of random samples. A phenomenological logistic growth model was fitted to the incidence data in adults (aged ≥15 years) and children (aged <15 years) in four regions in Estonia. Factors influencing the spread of the virus, such as policy measures, school holidays, the number of travel-related cases, and cumulative vaccination or infection rates, were tested as covariates in the model. Results The eleven most common lineages (one Alpha, six Delta, two Omicron BA.1, and two Omicron BA.2) caused 84.7% and 85.8% of all SARS-CoV-2 infections in children and adults, respectively, during the study period. According to the final model, the Delta variant had slower growth and a lower maximum cumulative incidence. The number of workplace closures in the previous week and school holidays in the same week decreased, but the number of travel-related cases in the same week increased the incidence growth. No difference between children and adults was observed. The testing rate was lower during school holidays than during school terms (median (IQR) 1964 (1437–2970) vs. 3136 (2476–4417) vs. per 100,000; p < 0.001). In 40.3% of the weeks, travel-related cases were detected, accounting for (IQR) 2.1% (0.9–4.3%) of the incidence of nontravel-related infections. Conclusion Our study suggests that the spread of SARS-CoV-2 infection was similar in children and adults. Workplace closures reduced transmission, whereas during school holidays lower testing contributed to a lower reported incidence, and travel-related cases were possibly underreported.